2003
DOI: 10.1021/bi030029q
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Aβ1-42into Globular Neurotoxins

Abstract: Amyloid beta 1-42 (Abeta(1-42)) is a self-associating peptide that becomes neurotoxic upon aggregation. Toxicity originally was attributed to the presence of large, readily formed Abeta fibrils, but a variety of other toxic species are now known. The current study shows that Abeta(1-42) can self-assemble into small, stable globular assemblies free of fibrils and protofibrils. Absence of large molecules was verified by atomic force microscopy (AFM) and nondenaturing gel electrophoresis. Denaturing electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
496
1
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(552 citation statements)
references
References 68 publications
48
496
1
7
Order By: Relevance
“…2a) and during the reconstitution of Ab in lipid bilayers (Fig. 3a) (Hafner et al 2001 ;Lin et al 2001 ;Chromy et al 2003 ;Klug et al 2003;Lashuel et al 2003 ;. The similar heights of the spheres, chain-like and annular protofibrils suggests that the spheres are the precursors of the others .…”
Section: Amyloid-b (Ab) (Alzheimer's Disease)mentioning
confidence: 84%
See 1 more Smart Citation
“…2a) and during the reconstitution of Ab in lipid bilayers (Fig. 3a) (Hafner et al 2001 ;Lin et al 2001 ;Chromy et al 2003 ;Klug et al 2003;Lashuel et al 2003 ;. The similar heights of the spheres, chain-like and annular protofibrils suggests that the spheres are the precursors of the others .…”
Section: Amyloid-b (Ab) (Alzheimer's Disease)mentioning
confidence: 84%
“…Any model for pathogenesis must explain these cases. It is important to emphasize that the wild-type proteins will also form amyloid pores in vitro, albeit more reluctantly than the disease-associated mutants (Hafner et al 2001;Ding et al 2002 ;Lashuel et al 2002aLashuel et al , b, 2003Shtilerman et al 2002 ;Chromy et al 2003 ;Chung, 2003 ;Klug et al 2003 ;. Factors other than mutations could trigger pore formation pathogenesis in sporadic disease (Fig.…”
Section: Mechanisms Of Protofibril Induced Toxicity In Protein Aggregmentioning
confidence: 99%
“…Results showed that void volume ( > 70 kDa) fractions selectively bound to the cell surface and processes of neurons. No such binding was reported for fractions containing monomers to tetramers, suggesting that advanced oligomer states, protofibrils, are more likely to be the culprit toxic species in ADDL preparation 67 . Subsequent solution-state characterization of ADDL preparations revealed that they consist of a heterogeneous population of Aβ species encompassing molecular sizes ranging from monomers to aggregates larger than 1 mDa, resembling the distribution observed for protofibrils.…”
Section: High Molecular Weightmentioning
confidence: 96%
“…ADDLs are soluble Aβ aggregates that, by atomic force microscopy, appear as spherical structures of 3-5 nm in diameter 15 . SEC was used to fractionate ADDLs and different fractions were compared for binding to the neuronal surface 67 . Results showed that void volume ( > 70 kDa) fractions selectively bound to the cell surface and processes of neurons.…”
Section: High Molecular Weightmentioning
confidence: 99%
“…Recently, extensive investigation of the aggregation pathway reveals that oligomeric assemblies and not mature fibrils are responsible for Aβ neurotoxicity (4)(5)(6)(7)(8)(9). Several approaches have been designed to target the Aβ assembly process in an effort to reduce toxic species in the brain.…”
mentioning
confidence: 99%